Developmental exposure to a mixture of unconventional oil and gas chemicals: A review of experimental effects on adult health, behavior, and disease. (1st August 2020) - Nagel, S.C.; Kassotis, C.D.; Vandenberg, L.N.; Lawrence, B.P.; Robert, J.; Balise, V.D.
Abstract: Unconventional oil and natural gas extraction (UOG) combines directional drilling and hydraulic fracturing and produces billions of liters of wastewater per year. Herein, we review experimental studies that evaluated the potential endocrine-mediated health impacts of exposure to a mixture of 23 UOG chemicals commonly found in wastewater. The purpose of this manuscript is to synthesize and summarize a body of work using the same UOG-mix but with different model systems and physiological endpoints in multiple experiments. The studies reviewed were conducted in laboratory animals (mice or tadpoles) and human tissue culture cells. A key feature of the in vivo studies was the use of four environmentally relevant doses spanning three orders of magnitude ranging from concentrations found in surface and ground water in UOG dense areas to concentrations found in UOG wastewater. This UOG-mix exhibited potent antagonist activity for the estrogen, androgen, glucocorticoid, progesterone, and thyroid receptors in human tissue culture cells. Subsequently, pregnant mice were administered the UOG-mix in drinking water and offspring were examined in adulthood or to tadpoles. Developmental exposure profoundly impacted pituitary hormone concentrations, reduced sperm counts, altered folliculogenesis, and increased mammary gland ductal density and preneoplastic lesions in mice. It also altered energy expenditure, exploratory and risk-taking behavior, the immune system in three immune models in mice, and affected basal and antiviral immunity in frogs. These findings highlight the diverse systems affected by developmental EDC exposure and the need to examine human and animal health in UOG regions. Highlights: Unconventional oil and gas (UOG) chemicals and wastewater disrupted hormone receptors. Perinatal exposure to a mixture of 23 UOG chemicals (UOG-mix) altered adult health. UOG-mix altered sperm counts, folliculogenesis, and pituitary hormones in adulthood. UOG-mix altered mammary gland morphology and induced precancerous lesions. UOG-mix altered frog antiviral immunity and the immune system in three mouse models.